The Queen's Grace: English Queenship, 1464-1503 - Neal, Derek (My University, 1996)
Medieval queenship, an institutionally and socially important condition marked by ambiguity and contradiction, is the subject of a growing body of research, to which this study's holistic approach seeks to make a valuable contribution by focusing on two queens consort of England between 1464 and 1503: Elizabeth Woodville and her daughter Elizabeth of York. The contemporary theory of queenship is elusive, combining the queen's subjection to her husband, and dissociation from the political sphere, with a marked legal independence and a versatile, powerful model in Marian symbolism, which stressed intercession as a priority for queens. This apparently incoherent conception is not easily understood through histories relying on narrative sources, whose evidence is scanty and vague. As a result, portrayals of both Elizabeth Woodville (negative) and Elizabeth of York (positive) have been determined by narrative attitudes toward gender and social status, which have accrued over generations of historical writing. The ceremonies of queenship (coronation, churching, royal entry, funerals), as prescribed for and enacted by both Queens Elizabeth, broadcast their role to the court and realm and to the queens themselves. They clearly established the queen's status as not equal to the king's, but also confirmed her autonomous authority (suggested by a general ceremonial separateness) and recognized her importance to the nation. That autonomy was made possible in a practical sense through the queen's landed estate and household, which enabled both queens to act as landed magnates and as patrons to different degrees; Elizabeth Woodville's greater resources allowed her to be the more active of the two. Moreover, the institutions of queenship enabled both queens to act as intermediaries between court and realm. Queens were very close to the centre of cultural and political life in fifteenth-century England, and are therefore significant figures requiring more sensitive, detailed studies.
Keywords: history; English queenship; 1464; 1503; Elizabeth Woodville; Elizabeth of York